SIMPLE METHOD FOR INVESTIGATION OF LOW FREQUENCY DAMPED OSCILLATIONS OF ELASTOMERS - TODICA, M.; POP, C. V.; BALIBANU, O. (Studia Universitatis Babeș-Bolyai Physica, 2016)
A simple method for digital data recording of mechanical low frequency oscillations has been proposed. The methods was applied to measurements the elastic constant, attenuation and viscosity coefficients of elastomers. Such parameters can be difficult measure by other methods for polymers with low flow, like the elastomers.